Ardan Radio Convergence As An Adaptation Of Private Radio In The Digital Era - Gissani, Muhammad Fikri; Sanusi, Nunung; Yulianti, Alin (JURNAL KOMUNIKATIO, 2024)
The digital age poses great challenges to traditional media institutions, including the radio industry. This research aims to examine the application of convergence by private radio institutions, particularly Radio Ardan, to navigate this dynamic landscape. Adaptation is key in facing fierce competition in the digital media landscape for survival and achievement of media goals. Radio Ardan, considering the number of listeners, the ranking of private radio stations in Bandung City, and its business strategy, is the center of attention of this research. The internet accelerates cultural shifts in media consumption, facilitates access to audio-visual information, and encourages the growth of alternative mass media platforms, significantly changing the traditional radio landscape. The resulting convergence model can serve as a guide for other private radio stations in Bandung City, helping them adapt to the challenges of the digital era and meet changing consumer preferences. Convergence involves the integration of traditional radio broadcasting with digital platforms such as online streaming, podcasts, social media engagement and mobile apps. By utilizing these various channels, radio stations can expand their reach, engage with audiences in new ways, and stay relevant amidst growing media competition. Through research and analysis of Radio Ardan's convergence efforts, it is hoped that it can provide useful insights and recommendations for other private radio institutions. By understanding and implementing effective convergence strategies, radio stations can increase competitiveness, maintain listener engagement, and secure their position in the ever-evolving media landscape in Bandung City and its surroundings. Adaptation and innovation are the keys to success in the face of these changes, while collaboration with digital platforms opens up new opportunities for the radio industry to spread its wings and continue to survive in the digital era.